Development, validation and reliability testing of a tool for assessing physical therapist competence in patient management - Sanggalang, Glenda V.
Clinical competence is a complex set of skills used by physical therapists (PTs) during daily patient management sessions. It is developed through PT education in the classroom and the workplace. With the country's transition toward use of outcome-based education, a gap was identified between standardization of PT program outcomes and corresponding assessment of student achievement. This study aimed to develop a tool for assessing PT competence during patient management in the Philippine setting using a mixed method, sequential exploratory design. National PT standards and assessment tools used in four local clinical affiliation centers were reviewed to describe the constructs and performance criteria used in assessing competence in patient management. These were validated based on 10 field experts' consensus on three Delphi surveys. Content validity was further established through consultation with an expert on tool development and through pilot testing. Psychometric properties of the tool were tested with 131 licensed PTs who work as either clinical instructors or classroom teachers in the Philippines. They used the developed tool to rate a videotaped session of PT student handling a simulated patient. The final version named Physical Therapy Competence in Patient Management (PT-CPM) tool has high internal consistency (Cronbach alpha = 0.912) and interrater reliability (ICC = 0.912) It has 31 items representing 7 constructs which were refined based on results for factor analysis. This valid and reliable tool can be used to assess competence of PTs during patient management in the Philippines, especially those in generalized clinical practice settings.